Guatemala : 2019 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2019)
Fundamentals remain strong and growth has revived after three years of subpar performance. Improved budgetary execution and monetary accommodation, broadly in line with past staff advice, are providing demand support as the economy navigates weaker terms of trade. Near-term growth is poised for a rebound on the back of fiscal impulse from the 2019 expansionary budget, exports recovery after last year's slump, and construction-driven investment. Lack of progress on long-delayed business climate and public sector reforms, the Sustainable Development Goals (SDG) agenda, and financial inclusion, dampen medium-term prospects.